Propuesta de rediseño del Mercado Municipal Bahía de Caráquez integrando una cubierta verde para mejora del paisaje urbano - Briones Abad, Cruz Antonio (2023)
At present, the lack of maintenance that the buildings for service use have suffered has been reflected in their facilities, allowing the population to propose changes or restructuring in their infrastructure and facilities, in our project a change in the distribution and restructuring is proposed. of the municipal market of Bahía De Caráquez, to improve the image of the city and the functionality that these types of establishments have in our community. The proposal counted with green roofs has become popular all over the world, especially in developed countries, as a viable tool for environmental management. Research on its technical requirements and its benefits is gaining space in universities and research centers, mainly in North America, Europe and Asia, and has multiplied remarkably since the 1990s to date. In the South American region there is little research in this regard. Only 2 publications on green roof research in Ecuador were found...............